Pharmacological management of orthodontic pain - Lopez, Pablo (2024)
Pain associated with orthodontic treatment, which is both frequent and challenging, primarily arises following procedures such as the placement of interproximal elastic separators and the installation of archwires. This pain is often due to inflammation of the periodontium, leading to discomfort. Effective pharmacological management is essential to enhance patient comfort throughout orthodontic treatment. Nonsteroidal anti-inflammatory drugs (NSAIDs) and acetaminophen are commonly employed due to their proven efficacy and safety profiles. These medications help reduce both inflammation and pain, thereby improving patient tolerance of orthodontic procedures. When selecting an analgesic, it is important to consider factors such as the intensity of pain, pre-existing medical conditions, and potential drug interactions. Careful and supervised use of these medications helps minimize risks and optimizes patient comfort during orthodontic care.